Vertical facial growth peaks before the age of 12 and their relation with pubertal development in 44 untreated Colombian mestizos - Jiménez-V., Iván Darío; Villegas-T., Luisa Fernanda; Álvarez-S., Luis Gonzalo (Revista Facultad de Odontología Universidad de Antioquia, 2013)
Introduction: most studies on facial growth focus on documenting and predicting pubertal growth, underestimating the description of growth before the age of 12. Although several studies on Caucasian populations have analyzed early growth peaks, none of the publications has related them with the pubertal peaks. Furthermore, no studies on Latin American mestizos are reported in the literature. Methods: since 1992, the Cleft Lip and Palate, Oral Physiology and Craniofacial Growth Research Group (CES-LPH for its Spanish initials) has been conducting a longitudinal study on facial growth in 44 untreated Colombian mestizos with a sample of 373 cephalic lateral radiographs obtained during a period of 18 years. Results: 21 of the 28 girls in the sample (75%) present major biennial increments of 5 mm in anterior face height (AFH) before age 12. In terms of posterior face height (PFH), there were 9 girls (32%) with biennial increases greater than 5 mm before 9 years old. 7 children (43%) presented biennial increases greater than 5 mm in AFH before the age of 12, and concerning PFH there were 9 children (56%) with the same behavior before the age of 12. For 5 girls and 3 boys (18%), this was the greatest growth peak throughout the follow-up period of a sample since the age of 6 until 19 years—a finding not previously reported in the literature—. Conclusions: early vertical growth peaks (AFH and PFH) in children younger than 9 years may explain the success of early functional jaw orthopedic therapies.